A Kinetic Study of Ex-situ Soil Remediation by Nickel Extraction Using Natural Deep Eutectic Solvent - Shahidah Nusailah Rashid; Hanee F. Hizaddin; Adeeb Hayyan; Shee En Chan; Khairunnisa Hasikin; Sarah Abdul Razak; Mohd Istajib Mokhtar; Muhammad Mokhzaini Azizan (Taylor and Francis Ltd., 2025)
Indexed by Scopus